A critical review of the production and advanced utilization of biochar via selective pyrolysis of lignocellulosic biomass. (September 2020) - Li, Yunchao; Xing, Bo; Ding, Yan; Han, Xinhong; Wang, Shurong
Graphical abstract: Highlights: In-situ pyrolysis regulation and post-modification of biochar were summarized. The relationship between physicochemical properties and applications of biochar was analyzed. The future research requirements for biochar preparation and applications were proposed. Abstract: Biochar is a carbon-rich product obtained from the thermo-chemical conversion of biomass. Studying the evolution properties of biochar by in-situ modification or post-modification is of great significance for improving the utilisation value of lignocellulosic biomass. In this paper, the production methods of biochar are reviewed. The effects of the biomass feedstock characteristics, production processes, reaction conditions (temperature, heating rate, etc.) as well as in-situ activation, heteroatomic doping, and functional group modification on the physical and chemical properties of biochar are compared. Based on its unique physicochemical properties, recent research advances with respect to the use of biochar in pollutant adsorbents, catalysts, and energy storage are reviewed. The relationship between biochar structure and its application are also revealed. It is suggested that a more effective control of biochar structure and its corresponding properties should be further investigated to develop a variety of biochar for targeted applications.